Bimetallic‐organic Frameworks CoMo‐ZIF‐67: An Efficient and Stable Catalyst for Selective Oxidation of Alkenes. Issue 1 (28th October 2020) - Zou, Wenhong; Guo, Yingxiong; Li, Pan; Liu, Mengying; Hou, Linxi
Abstract: Developing catalysts for the selective oxidation of alkenes with environment‐friendly, unique structural characteristics, high economic benefit and better catalytic performance is important. Herein, we employed ZIF‐67 as the sacrificial template to synthesize bimetallic‐organic frameworks Cox Mo100‐x ‐ZIF nanocages by a facile dissolution‐regrowth strategy. The Co51.8 Mo48.2 ‐ZIF catalyst was tested under various experimental parameters for the selective oxidation of cyclooctene to screen the optimal reaction conditions. Under the optimal reaction conditions, Co51.8 Mo48.2 ‐ZIF nanocages exhibited a high cyclooctene conversion of 99.3 % and a selectivity of 99.0 % to epoxy cyclooctane. Furthermore, Co51.8 Mo48.2 ‐ZIF nanocages can maintain their catalytic performance after reused five catalytic cycles. This bimetallic catalyst could also be used for the epoxidation of a wide range of alkenes, such as hexene or cyclohexene. In addition, the kinetic studies were conducted, and a reasonable reaction mechanism was proposed based on density functional theory calculations. The outstanding catalytic performance of Cox Mo100‐x ‐ZIF nanocages can be attributed to the cooperativity between Co and Mo sites and the hollow structure with high surface areas. Abstract : Bimetallic‐organic frameworks CoMo‐ZIF‐67 catalysts have been successfully synthesized. The catalyst can be used to catalyse the epoxidation of alkenes to generate epoxides and showed excellent performance. The catalyst can be easily separated from the reaction mixture and reused for many times. The activation energy was measured, and a plausible reaction mechanism was proposed based on density functional theory studies.